Estruturação socioambiental na microrregião de Boquim/SE - Silva, Alda Lisboa de Matos (2019)
Nature is fundamental for the development of societies, but this society-nature relationship has not always been harmonious, since it can generate changes that negatively impact landscapes with loss of original vegetation, pressure on water sources, biological uncontrol, biophysical and socioeconomic imbalance. The predatory actions that society imprints on landscapes can be seen in urban and rural environments, and manifest in multiple dimensions, from local to global. In this sense, the thesis aims to analyze the features and socioenvironmental changes of the landscape by the GTP system (Geosystem, Territory and Landscape) in the Microregion of Boquim/SE. The theoretical conceptual and methodological model proposed by Georges Bertrand studies the territory of the environment, based on three inputs: the geosystem is the source; territory is the resource; the landscape is identity. The method adopted was systemic, since it corroborates the understanding of the study of the geographic dynamics in an integrated way. From this reference, the following methodological procedures were used: bibliographical, documentary and field research. The study identified units of landscapes in anthropic Rhexistasy, Biostasy, and area with Regressive Dynamics. It was verified that the Microregion of Boquim presents an environmental structure marked by anthropic pressure, motivated by the economic potential of orange monoculture, a unique process formed by small family farms. The occupation of this territory was developed based on the implantation of small agricultural lots directed to citriculture, which at present is still the activity that goes through a period of market readaptation and is the mark of the landscape of this microregion. It was found that social actors carry the memories of this period of great dynamics of production as something promising for the future of the region. In the landscape, the marks of a great past and in the communities the struggle to overcome the challenges that permeate the citriculture in the context of the Microregion of Boquim. The environmental structure, and its biophysical characteristics, associated to the multiple forms of territoriality reveal the territorial aptitude and the socio-cultural